Parotid Gland Rupture in a Holstein-Friesian Cow - Sharma, Rohit K.; Mishra, Saloni; Kumar, Pawan; Das, Jagdish; Bishnoi, Anil K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In India, ruminants, especially cattle and buffaloes, are domesticated for milk purposes; however, some leather  industries and slaughterhouses also produce different  livestock products from the same animals. Trauma to the  salivary gland directly influences milk production of animals  either because of indigestion or dehydration. The common  salivary gland affections in ruminants are salivary fistula,  sialolith, ectasia of the parotid duct, and sialoceles (Misk and  Nigam, 1984; Misk et al., 1991; Semieka, 2002; Sagar et  al.,  2010). In ruminants, there are 3-paired salivary glands, viz., the  parotid, mandibular, and sublingual and trauma to salivary  gland infrequently occurs in cattle, may cause a wound  with salivary secretions and this leakage of saliva into the  surrounding tissue along with its local tissue reaction may  lead to the development of a circumscribed soft swelling  in the region (Singh et al. 2020). Quakes can quickly treat  many clinical problems under field conditions, but trauma to  the salivary gland requires special attention, and improper  management of such situations leads to the life-threatening  condition of the animal. Since cauterization of the gland  is an easy, economical, and feasible approach under field  conditions, the present case was planned for medicinal  attempt rather than surgical intervention.
Keywords: Parotid Gland Rupture; Holstein-Friesian; Cow